Patient Engagement in Primary Care: Family Medicine, Accessibility, and Doctor–Patient Relationship - Luthfi Primadani Kusuma; Aflit Nuryulia Praswati; Yusuf Alam Romadhon (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Patient engagement is a key determinant of effective primary care delivery, particularly in semi‑rural settings where access barriers and fragmented relationships often limit care continuity. Family medicine principles and improved homecare accessibility are frequently proposed strategies to enhance patient engagement, yet their combined mechanisms remain insufficiently synthesized. Objective: This study systematically reviews empirical evidence regarding how family medicine principles and homecare accessibility influence patient engagement, with particular attention to the mediating role of the doctor–patient relationship. Methods: A systematic review following PRISMA guidelines was conducted using Scopus, PubMed, and ScienceDirect databases for studies published between 2013 and 2025. Thirty‑eight eligible studies were included. Results: Evidence suggests that continuity of care, coordination, and comprehensive family medicine practice improve trust and sustained patient participation. Accessibility factors including time, distance, and cost determine the feasibility of service use. Relational factors—especially communication quality and physician empathy—consistently mediate structural effects on engagement. Conclusion: Patient engagement in primary care is strengthened when structural accessibility improvements are integrated with relational quality initiatives. Combined strategies involving continuity of care, access improvements, and clinician communication training offer the greatest potential to enhance patient‑centered primary care in semi‑rural settings.